Enhancing Post-Disaster Mapping Assessment: Agent-Based Simulation Modeling Integrating Ground Vehicles and Drones (Case Study: Mount Merapi's Volcanic Eruption) - Liperda, Rahmad Inca; Rinaldy, Ravi Prananda; Redi, Anak Agung Ngurah Perwira; Asih, Anna Maria Sri; Sopha, Bertha Maya (Jurnal Logistik Indonesia, 2023)
This research presents an agent-based simulation model for post-disaster location mapping, considering land vehicles and drones along with access road availability and depot locations. The study examines the impact of bridge facility damage on depot selection and time indicators. Results reveal that damage to bridge facilities affects depots differently based on their location, leading to increased total processing and completion times due to interactions between land vehicles and bridges. Depot 7 emerges as the optimal location for undamaged and KRB II and III damage scenarios based on total processing time. Depot 3 performs best for KRB III damage, while Depot 8 exhibits the shortest completion time across all scenarios. These findings emphasize the importance of selecting depots with resilient road access and alternative routes, improving post-disaster logistics efficiency.